KEGIATAN BERSIH-BERSIH LINGKUNGAN KAMPUS DAN PENGELOLAAN SAMPAH DALAM MEMBANGUN KESADARAN KEBERSIHAN MAHASISWA - Febrian Dirgantara; Muhammad Putra Alaikassalam; Didit Darmawan; Rafadi Khan Khayru; Alfa Thoyibah (INCIDENTAL : Journal Of Community Service and Empowerment, 2026)
This Community Service (PkM) activity aimed to enhance students’ awareness of the importance of maintaining campus environmental cleanliness through a collective campus clean-up program. The main issue addressed was the low level of students' concern for campus cleanliness, which negatively affects comfort, health, and the overall quality of the academic environment. The activity employed the Participatory Action Research (PAR) approach, involving students actively in the planning, implementation, reflection, and evaluation stages. Through this participatory approach, students acted not only as participants but also as key stakeholders who identified problems and collaboratively formulated appropriate solutions. The activities included campus clean-up actions, waste collection and sorting, and educational sessions on environmental cleanliness and proper waste management. The results indicated increased awareness, responsibility, environmental concern, and teamwork among students in maintaining campus cleanliness, thereby fostering a clean, healthy, comfortable, and sustainable academic culture.